The ex officio power of the arbitrator to raise new issues of law in Islamic finance disputes - Hassan, Mohamed (AUC Knowledge Fountain, 2019)
The legal nature of arbitration varies from the legal nature of litigation. While the judge derives his authority from the state power, the arbitrator derives his powers, in the first place, from the parties' agreement. The power of the court to raise new issues of law ex officio is widely recognized. When it comes to arbitration, the matter is more complicated. The ex officio power of the arbitrator to raise new issues of law is controversial in international commercial arbitration. The situation is even more complicated in contemporary Islamic finance disputes due to the nature of the applicable law to the merits of such disputes. Sharīʿa, which is the applicable law or a significant part thereof, obliges the arbitrator to apply the mandatory rules of Sharīʿa ex officio regardless of the parties' claims. Under Sharīʿa, the primacy is to its mandatory rules, contrary to international arbitration which grants the primacy to party autonomy. This sometimes results in a conflict between the rules of Sharīʿa and the rules of international arbitration. This paper examines to what extent the arbitrator may raise new issues of law ex officio in Islamic finance disputes. The paper argues that the arbitrator has a power, not a duty, to raise new issues of law ex officio in Islamic finance disputes; however, such a power is surrounded by considerable practical and legal challenges which may impede it. In doing so, the paper compares the scope of arbitrator's power between Islamic legal theory and international arbitration theory. It also examines and analyzes the available case studies which deal with the ex officio power of the arbitrator to raise new issues of law in Islamic finance disputes.